The value of the Social Responsability during the state of alarma - Solano Santos, Luis Felipe; Cuesta Díaz, Victoria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Many corporations assumed the role that corresponded to them during the pandemic and, more specifically, during the state of alarm decreed in Spain at the beginning of 2020, in terms of Corporate Social Responsibility. Although there are many who interpret this type of action as voluntary contributions or actions, in reality it is a matter of assuming a series of obligations included in the so called culture standard, which undoubtedly pay considerable dividends to the organization in terms of reputation and image.